Studying sorption properties of a mixture of natural and synthetic zeolites in respect of radionuclides ¹³⁷Cs and ⁹⁰Sr - Lonin, A.Ya.; Krasnopyorova, A.P. (Вопросы атомной науки и техники, 2009)
Sorption properties of a mixture of zeolites (natural and synthetic) in respect of radionuclides ¹³⁷Cs and ⁹⁰Sr are studied. The influence of additions on the sorption properties of clinoptilolite and mixture of zeolites (natural and synthetic) is studied. Вивчалися сорбційні властивості суміші цеолітів (природного і синтетичного) відносно радіонуклідів ¹³⁷Cs і ⁹⁰Sr. Досліджено впливи допоміжних речовин на сорбційні властивості кліноптілоліту і суміші цеолітів (природного і синтетичного). Изучались сорбционне свойства смеси цеолитов (природного и синтетического) в отношении радионуклидов ¹³⁷Cs и ⁹⁰Sr. Исследовано влияния вспомогательных веществ на сорбционные свойства клиноптилолита и смеси цеолитов (природного и синтетического).